2020
DOI: 10.1186/s13098-020-0520-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotype in Darier disease: a cross-sectional clinical study

Abstract: Background: Human data supporting a role for endoplasmic reticulum (ER) stress and calcium dyshomeostasis in diabetes is scarce. Darier disease (DD) is a hereditary skin disease caused by mutations in the ATP2A2 gene encoding the sarcoendoplasmic-reticulum ATPase 2 (SERCA2) calcium pump, which causes calcium dyshomeostasis and ER stress. We hypothesize that DD patients have a diabetes-like metabolic phenotype and the objective of this study was to examine the association between DD with impaired glucose tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Consistent with this observation, in individuals with Darier White disease, a rare genetic icthyosis disorder resulting from SERCA2 haploinsufficiency, lesion keratinocytes exhibit ER retention of cadherin, a transmembrane protein located at the plasma membrane that typically requires trafficking to the membrane (Celli et al ., 2012). Only one group has examined proinsulin to insulin ratios in individuals with Darier White; they described a non-significant trend towards increased ratios in a small cohort of affected individuals compared to matched controls (Ahanian et al, 2020). This same group found that individuals with Darier White have an increased relative risk of developing T1D (Cederlöf et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this observation, in individuals with Darier White disease, a rare genetic icthyosis disorder resulting from SERCA2 haploinsufficiency, lesion keratinocytes exhibit ER retention of cadherin, a transmembrane protein located at the plasma membrane that typically requires trafficking to the membrane (Celli et al ., 2012). Only one group has examined proinsulin to insulin ratios in individuals with Darier White; they described a non-significant trend towards increased ratios in a small cohort of affected individuals compared to matched controls (Ahanian et al, 2020). This same group found that individuals with Darier White have an increased relative risk of developing T1D (Cederlöf et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In medical literature, HHD has not been found to be associated with extradermal symptoms, while, as previously noted, there is strong evidence for a direct link between DD and psychiatric and intellectual disabilities. Our group has recently published reports shedding further light on DD as a multi-organ disease, showing associations with type 1 diabetes and pancreatic beta-cell dysfunction, as well as heart failure ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, in the recent cross-sectional clinical study of metabolic phenotype of DD, it has been found that DD patients have lower fasting glucose level and higher c-peptide and HOMA2-%beta compared to their matched control group. 33 This indicates that DD patients have a higher secretory capacity of islet cells and a higher basal insulin level. The authors emphasize that increased basal insulin is associated with worse control of glucose, and with time, may lead to type 2 diabetes.…”
Section: Dd and Diabetesmentioning
confidence: 98%
“…The authors emphasize that increased basal insulin is associated with worse control of glucose, and with time, may lead to type 2 diabetes. 33 The relationship between glucose metabolism and DD may be due to the fact that among different SERCA isoforms, SERCA2b is most abundantly expressed in pancreatic beta-cells. 14 It has been shown that the loss of SERCA2b due to mutations in ATP2A2, as seen in individuals with DD, leads to secretory dysfunction, and defect in proliferation and survival of beta-cells.…”
Section: Dd and Diabetesmentioning
confidence: 99%